PtI2-catalyzed cyclization of 3-acyloxy-1, 5-enynes with the elimination of HOAc and a benzyl shift: synthesis of unsymmetrical m-terphenyls1. Issue 15 (21st April 2015) - Huang, Kaimeng; Ke, Xiaona; Wang, Hongkai; Wang, Junying; Zhou, Chenchen; Xu, Xiufang; Liu, Lingyan; Li, Jing
<x xml:space="preserve">Abstract</x> A new cyclization of 1, 5-enyne was developed to synthesize the m-terphenyls via the elimination of HOAc and a benzyl shift.